2014
DOI: 10.1128/jvi.03241-13
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Involvement and Therapeutic Implications of Host Cellular Factors in Hepatitis C Virus Cell-to-Cell Spread

Abstract: Hepatitis C virus (HCV) infects 180 million people worldwide and is a leading cause of liver diseases such as fibrosis, cirrhosis, and hepatocellular carcinoma. It has been shown that HCV can spread to naive cells using two distinct entry mechanisms, "cellfree" entry of infectious extracellular virions that have been released by infected cells and direct "cell-to-cell" transmission. Here, we examined host cell requirements for HCV spread and found that the cholesterol uptake receptor NPC1L1, which we recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 63 publications
1
57
0
Order By: Relevance
“…This is consistent with the report from Barretto et al 33 Engineering nonhepatic cells to produce HCV through ectopic apoE expression can confer cell-to-cell transmission capacity, albeit to a limited degree relative to the levels observed in the current study. 34 We thus cannot exclude that epitopes not recognized by the utilized anti-apoE antibody play a role in cell-to-cell transmission or that this antibody may have limited access to the virus during this process.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with the report from Barretto et al 33 Engineering nonhepatic cells to produce HCV through ectopic apoE expression can confer cell-to-cell transmission capacity, albeit to a limited degree relative to the levels observed in the current study. 34 We thus cannot exclude that epitopes not recognized by the utilized anti-apoE antibody play a role in cell-to-cell transmission or that this antibody may have limited access to the virus during this process.…”
Section: Discussionsupporting
confidence: 82%
“…However, our results indicate that significant differences exist between the abilities of ApoB and ApoE to mediate this route of infection. It is important to note that a previous study reported that ApoB or ApoE depletion had no effect on HCV cell-cell spread (34). We interpret this divergence in terms of differences in the experimental approaches: e.g., the duration of the experiment (5 days p.i.…”
Section: Discussionmentioning
confidence: 79%
“…However, this is controversial since another study described that ApoE, ApoB, and microsomal triglyceride transfer protein (MTP) are not involved in this type of infection (34). By blocking cell-free infectivity, we show that blocking ApoE in donor cells inhibits cell-to-cell HCV infection.…”
mentioning
confidence: 80%
“…One report stated that the lack of apolipoprotein E (ApoE) expression in a nonhepatic cell line blocked HCV cell-to-cell transmission (31). In contrast, knockdown of ApoE, ApoB, and microsomal triglyceride transfer protein (MTP) did not block efficient cell-to-cell transmission (32). Whether HCV assembly parts play an important role in cell-to-cell transmission has not been clearly determined due to the lack of a straightforward cell system which enables live-cell distinctions between donor and recipient cells during HCV cell-to-cell transmission.…”
mentioning
confidence: 99%